2022
DOI: 10.3389/fnut.2021.805465
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella histicola Mitigated Estrogen Deficiency-Induced Depression via Gut Microbiota-Dependent Modulation of Inflammation in Ovariectomized Mice

Abstract: BackgroundEstrogen deficiency-induced depression is closely associated with an imbalance in intestinal microbiota and inflammation. Prevotella histicola (P. histicola), an emerging probiotic, apparently improves inflammatory responses. This study aims to verify the antidepressant-like effects of P. histicola and clarify its potential mechanisms.MethodsMice were treated with P. histicola and cohousing after ovariectomy (OVX). The changes in depression-like behaviors among mice were examined by behavioral tasks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Previously, P. histicola was reported to attenuate multiple sclerosis [33] and arthritis [34] in the animal models. Of note, P. histicola reshapes gut microbiota and upregulates tight junction proteins ZO-1, Occludin and Claodin-1 to prevent gut leak against central neural in ammation in ovariectomy mice [35]. The gastric microbiota was evidenced the importance of the gastric mucosal integrity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, P. histicola was reported to attenuate multiple sclerosis [33] and arthritis [34] in the animal models. Of note, P. histicola reshapes gut microbiota and upregulates tight junction proteins ZO-1, Occludin and Claodin-1 to prevent gut leak against central neural in ammation in ovariectomy mice [35]. The gastric microbiota was evidenced the importance of the gastric mucosal integrity [36].…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory mediators can further mediate changes in the intestinal flora and disturbances in their metabolites, affecting brain function and depression. Estrogen deficiency can cause depression-like behavior, and Huang et al (44) found in their experiments that estrogen deficiency-induced depression was associated with intestinal flora imbalance and inflammatory response in mice undergoing ovariectomy (OVX), where intestinal flora imbalance caused (45). There is growing evidence that modulation of BDNF expression levels can exert antidepressant effects (46)(47)(48), where BDNF-cAMP response element binding protein (CREB) signaling is one of the most attractive signaling pathways for the treatment of depression (49,50).…”
Section: Intestinal Flora Dysbiosismentioning
confidence: 99%
“…These inflammatory mediators can further mediate changes in the intestinal flora and disturbances in their metabolites, affecting brain function and depression. Estrogen deficiency can cause depression-like behavior, and Huang et al ( 44 ) found in their experiments that estrogen deficiency-induced depression was associated with intestinal flora imbalance and inflammatory response in mice undergoing ovariectomy (OVX), where intestinal flora imbalance caused leaky gut and central inflammation (downregulation of COX-2 expression) to suppress BDNF expression in hippocampal neurogenesis, resulting in depressive behavior in OVX mice. BDNF is a neuroprotective molecule that plays a key role in neuroplasticity, neuroinflammation, learning and memory ( 45 ).…”
Section: Cyclo-oxygen-ase-2 Roles In the Pathogenesis Of Depressionmentioning
confidence: 99%
“…Furthermore, apple phenolic extract improved lead acetate-induced depression-like behaviors through attenuating neuroinflammation and neuronal apoptosis, which was associated with the miR-22-3p/sirtuin 1 (SIRT1) signaling pathway [ 39 ]. In an ovariectomy mice model, the oral application of Prevotella histicola improved estrogen deficiency-induced depression through downregulating the expression levels of the vascular cell adhesion molecule (VCAM), macrophage chemoattractant protein 1 (MCP-1), IL-6, IL-8, and TNF-α in the ileum and colon of mice [ 44 ]. Moreover, Lacticaseibacillus paracasei NK112 exerted protective effects against Escherichia coli -induced depression through decreasing the expression of IL-1α, IL-6, and TNF-α, and inhibiting the activity of NF-κB in the hippocampus [ 45 ].…”
Section: Depressionmentioning
confidence: 99%
“…A number of studies have pointed out that several probiotics could improve the symptoms of depression. For example, Prevotella histicola was an emerging probiotic and showed a protective effect against estrogen deficiency-induced depression by elevating the abundance of intestinal flora, especially Akkermansia and Lactobacillus [ 44 ]. Moreover, Lactobacillus casei exerted anti-depressive effects on postpartum depression via changing the composition of gut microbiota, increasing the expression level of BDNF, and suppressing the activity of the BDNF–MAPK pathway [ 77 ].…”
Section: Depressionmentioning
confidence: 99%